Identification and characterization of Chhattisgarhi buffalo population in India - VOHRA, VIKAS; SINGH, MOHAN; MUKHERJEE, K; KATARIA, R S (The Indian Journal of Animal Sciences, 2017)
Chhattisgarhi buffalo are raised in North and Central parts of Chhattisgarh. They are medium sized buffaloes having triple purpose utility viz. milk, drought and manure, which makes them economical to their keepers. Average milk production in buffaloes was around 4 kg/day with a peak milk yield of 6 kg and buffalo bullocks were preferred over cattle bullocks for cultivating rice fields. Physical and phenotypic characterization of Chhattisgarhi buffalo reveals that the population does not resemble other extant breeds of the region and has a unique management system, therefore, we may conclude that Chhattisgarhi buffalo is unique and distinct population. We recommend that Chhattisgarhi buffalo should be registered and recognized as separate breed of buffalo in India.